Skill utilization at work: Opportunity and motivation - Giovanni Russo (IZA World of Labor, 2017)
Organizational characteristics and management styles vary dramatically both across and within sectors, which leads to huge variation in job design and complexity. Complex jobs pose a challenge for management and workers; an incentive structure aimed at unlocking workers' potential can effectively address this challenge. However, the heterogeneity of job complexity and the inherent difficulty in devising a correct set of incentives may result in misalignment between job demands and incentivized behaviors, and in complaints by employers about the lack of skilled workers.
Keywords: J24; 330; job demands; skills; tasks; skill utilization; incentives